Perceptions and preferences for fresh seafood in an Australian context - McManus, Alexandra; Hunt, W.; Storey, Jessica; McManus, Jennifer; Hilhorst, S. (Wiley-Blackwell Publishing Ltd., 2014)
Seafood as a whole food is highly nutritious. It is an important dietary source of protein, omega-3 fatty acids and a wide array of highly bioavailable micronutrients. Despite the established health benefits associated with fish and seafood consumption, in Australia consumption levels still remain below those recommended for health. Although considerable research has been carried out on enablers and barriers to seafood consumption, the reasons Australian consumers do not consume recommended amounts of seafood while stating they would like to consume more seafood are complex and have not been fully illuminated. This paper reports on the development and results of a self-administered questionnaire that aimed to identify consumer perceptions and preferences for fresh and frozen seafood. Data were collected through intercept surveys at an Australian university and 239 valid responses were received. Results confirmed respondent preference for fresh fish and seafood. There was significant confusion among respondents about what constitutes fresh seafood, with the term ‘fresh’ having different meanings to different respondents. Over half of respondents understood the term fresh to relate to seafood having been caught that same day. In comparison, approximately 15% understood fresh to reflect the accepted definition of having never been frozen. Additionally, results indicated respondents find it difficult to recognize if seafood is fresh, particularly in comparison with other meats. There is significant potential for the development of regulations for labelling of unpackaged seafood in order to allow consumers to make informed decisions about their purchases.